2014
DOI: 10.1177/1461444814521140
|View full text |Cite
|
Sign up to set email alerts
|

Maintaining and losing control during internet gambling: A qualitative study of gamblers’ experiences

Abstract: This paper provides an in-depth exploration of the psychosocial factors and processes related to maintaining and losing control during internet gambling. It explores features of internet gambling leading to loss of control, control strategies used by internet gamblers, and the perceived utility of online responsible gambling measures. Interviews with 25 moderate risk and problem internet gamblers yielded rich first-person accounts analysed using interpretative phenomenological analysis. The most frequently ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
89
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 82 publications
(104 citation statements)
references
References 29 publications
8
89
0
1
Order By: Relevance
“…The vast majority of Internet bettors seem to be able to regulate themselves and require little additional safeguards. Hing et al (2015a) reported that the use of digital money contributed to higher rates of gambling and loss of control. Participants made greater use of self-limiting strategies than those available on gambling websites, such as deposit limits and self-exclusion.…”
Section: Setting Gambling Limitsmentioning
confidence: 99%
“…The vast majority of Internet bettors seem to be able to regulate themselves and require little additional safeguards. Hing et al (2015a) reported that the use of digital money contributed to higher rates of gambling and loss of control. Participants made greater use of self-limiting strategies than those available on gambling websites, such as deposit limits and self-exclusion.…”
Section: Setting Gambling Limitsmentioning
confidence: 99%
“…The gambling study literature has suggested that in-play sports betting may offer more of a risk to problem gamblers because it allows the option for high-speed continuous betting and requires rapid and impulsive decisions in absence of time for reflection (Hing et al 2014a(Hing et al , 2014b(Hing et al , 2014cLopez-Gonzalez et al, 2017a, b, c, d;Nelson et al 2008). Therefore, in relation to problem gambling, in-play betting offers structural factors that may contribute to the development of gambling-related problems.…”
Section: Discussionmentioning
confidence: 99%
“…Here, gamblers who were reminded to consider using a time limit tool spent considerably less time gambling than those who did not receive this reminder. A study by Hing et al (2015a) also emphasised the tendency of regular gamblers to go beyond self-imposed limits, which suggests that online gamblers would benefit from limit-setting mechanisms imposed by online gambling websites.…”
Section: Responsible Gambling Toolsmentioning
confidence: 99%